The role of clinician assistants in addressing perinatal depression - Katherine M. Cooper; Grace A. Masters; Tiffany A. Moore Simas; Nancy Byatt (Taylor & Francis Group, 2022)
Background Upwards of one in seven individuals experience perinatal depression and many individuals cannot access treatment. In response, perinatal depression is increasingly being managed in the obstetric setting. This study aimed to characterize the experiences of clinicians and clinician assistants to inform the extent to which clinician assistants can help address depression in obstetric settings. Methods This cross-sectional analysis used data from an ongoing cluster randomized control trial: The PRogram In Support of Moms (PRISM). Participants included clinicians (physicians, certified nurse midwives, nurse practitioners) and clinician assistants (medical assistants, nursing assistants). Baseline data regarding practices and attitudes of clinicians and clinician assistants toward addressing depression in the obstetric setting were described. Logistic regressions were used to examine the association of clinician time to complete work and depression management. Results Clinician assistants experienced significantly fewer time constraints than did clinicians. However, having adequate time to complete work was not significantly associated with increased depression management in clinicians. Clinician assistants reported feeling that addressing depression is an important part of their job, despite variation in doing so. Conclusion Clinician assistants are interacting with perinatal women extensively and are a vital part of obstetric care workflows. Clinician assistants report that they want to address depression and have time to do so. Thus, clinician assistants may be poised to help address the mental health needs of perinatal individuals.